A Wearable Footwear System with Visual and Tactile Cueing for Freezing of Gait Management across ON and OFF States in Parkinson’s Disease - Anusha, M. U.; Rani, K. Uma; Rao, Kishor Manohar; Nemichandra, S. C.; Ramesh, Jayashree; Saraswathi, Purohit (Engineering, Technology & Applied Science Research, 2026)
Freezing of Gait (FoG) is a disabling motor symptom of Parkinson’s Disease (PD) that commonly occurs during OFF-medication states and is strongly associated with falls and reduced quality of life. This study presents a smart shoe system, a wearable assistive device that delivers synchronized visual and tactile cues to improve gait regularity. The dual-cue mechanism projects a laser line during the stance phase and provides vibration feedback during the swing phase, thereby supporting step initiation and mitigating FoG episodes. Quantitative gait parameters, including step count, cadence, and step initiation delay, were measured and analyzed using comparative heatmaps to visualize ON/OFF state variations. The integrated safety features include fall detection using an MPU6050 inertial sensor, GPS-based location tracking, and real-time data transmission to the ThingSpeak Internet of Things (IoT) platform for remote monitoring. Clinical trials demonstrated significantly higher cue dependence in the OFF state, confirming the system’s compensatory role when medication efficacy is diminished. Beyond motor improvement, reducing FoG episodes may also alleviate FoG-related anxiety, thereby enhancing the overall well-being of patients. The proposed system demonstrates a cost-effective and clinically relevant solution for rehabilitation, fall prevention, and remote monitoring, with potential scalability for Artificial Intelligence (AI)-enabled personalized PD management.